2006
DOI: 10.1509/jmkg.70.1.137.qxd
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction, Job Performance, and Effort: A Reexamination Using Agency Theory

Abstract: The objective of this article is to clarify ambiguities in the literature regarding the relationships among three key constructs of work relationships: effort, job performance, and job satisfaction. The relationship between job performance and job satisfaction is of central interest to research in organizational psychology. However, empirical research in that area finds that the link between these constructs is weak at best. A negative effect of effort on job satisfaction is consistent with agency theory, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
97
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(129 citation statements)
references
References 36 publications
15
97
0
5
Order By: Relevance
“…Finally, as proven in the studies by Christen et al (2006) and Frey et al (2013), this study supported H4 and H5, as hypothesized. Perceived job performance was positively associated with job satisfaction (H4: ␤ = 0.26, t = 2.36), and job satisfaction was positively associated with employee retention (H5: ␤ = 0.60, t = 5.50), which indicated that perceived job performance had a positive effect on job satisfaction, such enhanced job satisfaction, leading to employee retention.…”
Section: Hypothesis Testingsupporting
confidence: 85%
See 2 more Smart Citations
“…Finally, as proven in the studies by Christen et al (2006) and Frey et al (2013), this study supported H4 and H5, as hypothesized. Perceived job performance was positively associated with job satisfaction (H4: ␤ = 0.26, t = 2.36), and job satisfaction was positively associated with employee retention (H5: ␤ = 0.60, t = 5.50), which indicated that perceived job performance had a positive effect on job satisfaction, such enhanced job satisfaction, leading to employee retention.…”
Section: Hypothesis Testingsupporting
confidence: 85%
“…Even though many previous studies (i.e., Bagozzi, 1980;Christen et al, 2006;Frey et al, 2013;Kumar et al, 2014) have shown significant relationships among job performance, satisfaction, and retention, this study reconfirms these relationships in the context of mobile device use at hotels. In order to retain capable, happy, and qualified employees, hotel management must be alert to their employees' basic and fundamental needs for performing their tasks efficiently and effectively; moreover, management must be mindful of whether they can thoughtfully implement employees' desired requests for shared goals.…”
Section: Practical Implicationssupporting
confidence: 76%
See 1 more Smart Citation
“…Due to their immediate effect, any impact of expectations on satisfaction or turnover may be easier to detect in this firm than in one with a more complex reward system that depends on behavioral inputs. Further, we note the importance of including performance-based compensation in our model to capture its impact on job satisfaction (Christen, Iyer, & Soberman, 2006).…”
Section: The Impact Of Compensationmentioning
confidence: 99%
“…On the whole, the literature suggests a positive impact of performance on job satisfaction (e.g., Christen et al, 2006). "Apparently, salespeople are motivated by the anticipated satisfaction that comes with performance more than they are by the performance itself" (Bagozzi, 1980, p.70).…”
Section: The Influence Of Salesperson Satisfactionmentioning
confidence: 99%